PERAN KARTU KREDIT DAN PROMOSI PENJUALAN DALAM MEMODERASI PENGARUH KUALITAS WEBSITE TERHADAP IMPULSIVE BUYING - Ningsih, Nova Widya; Nandya Oktora Panasea, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p07, 2023)
Shopee is the second largest e-commerce in Indonesia. This increasingly easy buying and selling process affects the occurrence of impulse buying. Purchases made without a plan before the purchase process is carried out are called impulsive buying. There are various variables behind impulsive buying, including the quality of the website which is influenced by the use of credit cards and sales promotions. This study was conducted to examine the role of credit card use and sales promotion in moderating the influence of website quality on impulsive buying. 110 Shopee website users in Denpasar City were involved in this study. This study was analyzed with the Partial Least Square (PLS) approach, and resulted that the quality of the website had a positive on impulsive buying, the use of credit cards had a positive on impulsive buying, sales promotions had a positive on impulsive buying, credit card use does not significantly strengthen the influence of website quality on impulsive buying, and sales promotions do not significantly strengthen the influence of website quality on impulsive buying. The implication of this research is as a solution recommendation to Shopee in increasing impulsive buying behavior by improving website quality, using credit cards, and selling promotions.